Pedagogy and Theology in Cyberspace: “All That We Can’t Leave Behind. . .” - Hess, Mary E. (Teaching theology and religion, 2002)
The questions raised by the integration of digital technologies into theology and pedagogy are broader than simple questions of how to use a particular tool. Instead, this integration raises cultural questions that require cultural interventions in response. Shweder's notion of “thinking through others” provides an evocative framework for envisioning more complex pedagogical responses. This essay is based on a presentation delivered to the first annual conference on Theology and Pedagogy in Cyberspace, held in Evanston, Illinois on 19–20 April 2001.